Advancement in prediction of shear strength and stiffness of cross laminated timber beams. (1st July 2021) - Jeleč, Mario; Dokšanović, Tihomir; Draganić, Hrvoje; Rajčić, Vlatka
Highlights: Improved analytical model and design proposals for CLT beams are reviewed. Design proposals for shear mode III are expanded for CLT with 7 layers. Experimentally obtained shear strength is successfully predicted by design proposals. Position of critical crossing area coincide between design proposals and DIC system. Experimentally obtained shear stiffness is successfully predicted by design proposals. Abstract: Cross laminated timber (CLT) beams are mainly used within wall panels, but also standalone in design situations where cross layers have a reinforcing effect concerning stress perpendicular to the beam axis. The stress state in CLT beam members is complex and shear failure is mainly governed by stresses and strains acting in the crossing areas between orthogonally bonded laminations, known as shear failure mode III. The current model suggested for the next version of Eurocode 5 regarding shear strength prediction has certain limitations. Based on model improvement, design proposals regarding shear failure mode III for CLT beams composed of 3 and 5 layers are expanded for CLT with 7 layers. Based on test results of small shear specimens, both design proposals successfully predict shear strength experimentally obtained on beam specimens. Evaluated full-field deformations by a digital image correlation (DIC) system and the improved model and design proposal coincide in regards to the critical crossing area position. The influence of reduced lamination widths on beam shear strength and shear strength ratio on the position of critical crossing areas are further analysed indicating a fairly minor contribution. The improved analytical model and design proposals were further modified to calculate the effective shear modulus of CLT beams. A good agreement between the analytical and test results is obtained for the slip modulus of the crossing areas proposed in the literature. However, a higher slip modulus seems appropriate for both design proposals in the design situation to avoid too conservative effective shear modulus and corresponding shear stiffness.